Silicon solar cells with heterojunction emitters and laser processed base contacts. (September 2017) - Jin, Chen; Martín, Isidro; López, Gema; Harrison, Samuel; Masmitja, Gerard; Ortega, Pablo R.; Alcubilla, Ramon
Abstract: In this work, we report on a novel structure of Interdigitated Back-Contacted (IBC) solar cells on c-Si p-type substrates that combines laser processed homojunction base contacts and silicon heterojunction (SHJ) emitters. These hybrid devices which can lead to potential benefits in device processing and/or conversion efficiency. In the proposed fabrication process special attention has been paid to the compatibility of both involved technologies: silicon heterojunction and laser doping from dielectric films. In particular, we focus on the surface passivation obtained by the heterojunction emitter after removing the aluminum oxide/silicon carbide (Al2 O3 /SiCx ) layer stack needed for the laser doping process and previously deposited on the c-Si surface. A severe passivation degradation after plasma etching process to remove the top SiCx film is observed, despite leaving the Al2 O3 film on the c-Si surface. Based on high-frequency capacitance-voltage characterization, an increase in the interface state density and a strong impact on the fixed charge density is deduced. Next, in order to choose an optimized metallization technology that could simultaneously contact both the ITO film and the p + laser processed regions, we evaluate the contact quality of Titanium and Aluminum on ITO. Results show that Titanium is a better option with a specific contact resistance of 1.1 mΩ cm 2 . Finally, finished hybrid IBC solar cells with conversion efficiencies in the 18-19% range are reported.